A Brief Introduction to Q Methodology - Yang, Yang (My University, 2016)
Q methodology is a method to systematically study subjective matters such as thoughts and beliefs on any given topic. Q methodology can be used for both theory building and theory testing. The purpose of this paper was to give a brief overview of Q methodology to readers with various backgrounds. This paper discussed several advantages of Q methodology that makes it attractive to researchers and practitioners who are interested in understanding different perspectives or behavioral patterns toward any given topic, its distinct position as a methodology, and how it fits into the qualitative—mixed—quantitative continuum. The paper further used two research studies as applications to demonstrate how to perform a Q methodological study, involving the following steps: development of the Q sort statements; selection of the P set (participants); Q sorting; and analysis and interpretation of Q sorts.
Citation: Yang, Y. (2016). A brief introduction to Q methodology. International Journal of Adult Vocational Education and Technology [Special Issue]: Quantitative and Mixed-Method Research, 7(2), 42-54. doi: 10.4018/IJAVET.2016040104
Keywords: Mixed Methods; Q Methodology; Qualitative Continuum; Subjectivity